Evaluation of sagittal inclination of occlusal plane and horizontal condylar guidance using various anterior reference points on arcon and nonarcon articulators - Jayant N Palaskar; Nikhil P Joshi; Amit D Hindocha; Anuja P Gunjal; Ketaki D Balsaraf (Wolters Kluwer Medknow Publications, 2022)
Aim: The aim of the study was to determine the effect of different anterior reference points during facebow transfer, on sagittal inclination of occlusal plane (SIOP) and horizontal condylar guidance (HCG) values obtained on arcon and nonarcon articulators. Materials and Methods: Facebow records of 25 participants were made and transferred to Hanau Wide-Vue (WV) and Hanau H2 (H2) articulators using conventional indirect transfer (CIT), superior annular groove (SAG), and inferior annular groove (IAG) as anterior reference points. Maxillary casts were mounted on each articulator followed by mandibular mountings. Protrusive interocclusal record was used to determine HCG, and SIOP was measured as an angle between the occlusal plane of mounted maxillary cast and upper member of the articulator. Both, HCG and SIOP were measured on a digital lateral cephalogram and the values obtained were compared with previously determined values from both the articulators. Intergroup comparison was done by analysis of variance and pair-wise comparison by Tukey post hoc test. Results: Values of SIOP significantly (P = 0.00) changed on both the articulators when CIT, SAG, and IAG were the anterior reference points. The ratio of SIOP and HCG on both articulators was comparable to that of the cephalogram for CIT, IAG, but it was substantially low for SAG. Conclusions: The variation of anterior reference point changes the value of SIOP recorded on Hanau WV and H2 articulators; however, it had no effect on HCG values recorded on both the articulators. The angle between SIOP and HCG changed with variations in superior-inferior position of the mountings on both articulators.